INFLUENCE OF ADDING POLYPROPYLENE(PP) INTO POLYETHYLENE(PE) ON MECHANICAL PROPERTIES OF GEOCELLS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
In the article, it will be considered what is the influence of the addition of 10% PP into a polyethylene mixture compared to a mixture of polyethylene on the main mechanical characteristics of geocells - hardness, maximum tensile strength, strength of the internal structural junctions (welds). It will be analyzed the interrelationships between the measured mechanical parameters.